Workshop Peningkatan Organization Image SDN 2 Mojosari Kabupaten Rembang - Febrianur I. F. S. Putra; Suhita W. Setyahuni; Mahmud Mahmud; Awanis L. Haziroh (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2023)
A good organization image is one of the factors for an organization to be able to achieve competitive advantage. To create a good image of an organization, an effective communication process is needed to the public. Online communication media and social media are effective organizational communication tools and can improve the organization's image. This community service activity is packaged in the form of training which aims to improve the skills of SDN 2 Mojosari teachers in mastering online media and social media as a means of organizational communication. Effective organizational communication can create a good image of the organization. This training activity has an impact on increasing the abilities of teachers and changing digital-based organizational communication strategies to improve the organization's image as one of the organization's competitive advantages.Organization image, Social Media, Organization Communication, Competitive Advantage